An investigation of movement dynamics and muscle activity during traditional and accentuated-eccentric squatting - Armstrong, R.; Baltzopoulos, V.; Langan-Evans, C.; Clark, D.; Jarvis, J.; Stewart, C.; O´Brien, T. (PLOS ONE, 2022)
Introduction Accentuated-eccentric loading (AEL) takes advantage of the high force producing potential of eccentric muscle contractions, potentially maximising mechanical tension within the muscle. However, evidence is lacking on how AEL squatting may load the involved musculature, limiting scientifically justified programming recommendations. The purpose of this study was to investigate the effects of concentric and eccentric loads on joint loading and muscle activity of the lower limbs. Methods Resistance trained males performed traditional squatting (20-100% of concentric one-repetition maximum [1RM]) and AEL squatting with eccentric loads (110-150% of 1RM) provided by a novel motorised isotonic resistance machine (Kineo). Kinetics and kinematics of the hip, knee, and ankle joints were collected, with electromyography from the gluteus maximus, vastus lateralis, biceps femoris, and gastrocnemius medialis. A secondary cohort underwent a kinematic and electromyography analysis of squatting technique to compare Kineo and back and front barbell squatting. Results Knee joint peak eccentric moments occurred at 120% 1RM (P = 0.045), with no further increase thereafter. As eccentric load increased, the time course of moment development occurred earlier in the eccentric phase. This resulted in a 37% increase in eccentric knee extensor work from the 80% 1RM trial to the 120% 1RM trial (P<0.001). Neither hip nor ankle joints displayed further change in kinetics as eccentric load increased above 100% 1RM. Electromyographic activity during traditional squatting was ~15-30% lower in all eccentric trials than in concentric trials for all muscles. EMG plateaued between a load of 80-100% 1RM during the eccentric trials and did not increase with AEL. No significant differences in kinematics were found between Kineo and barbell squatting. Conclusions The knee extensors appear to be preferentially loaded during AEL squatting. The greater work performed during the eccentric phase of the squat as eccentric load increased suggests greater total mechanical tension could be the cause of adaptations from AEL. Our data suggest that AEL should be programmed with a load of 120% of 1RM. Further studies are needed to confirm the longer-term training effects of AEL.